2020
DOI: 10.1111/fare.12518
|View full text |Cite
|
Sign up to set email alerts
|

Parenting Among Rohingya and Afghan Refugee Parents Residing in Malaysia

Abstract: Objective This study examined the measurement properties of parenting‐related measures among 140 Rohingya and Afghan refugee parents residing in Malaysia, then examined factors associated with these parenting outcomes. Background Unprecedented numbers of forced migrant families reside in countries of first asylum with temporary status and limited legal rights. Limited research examines parenting experiences among these communities. Method To examine construct validity and reliability of parenting‐related measu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(11 citation statements)
references
References 60 publications
0
10
0
Order By: Relevance
“…We found that younger students, particularly those with poor language skills have difficulty following virtual lessons and would benefit from parental guidance in the absence of a teacher. Unfortunately, non-citizen parents with low educational attainment, like the Rohingya refugees in Malaysia [ 54 , 55 ], may be less able to support children with home education and online learning [ 43 , 56 – 58 ]. Studies elsewhere have linked various dimensions of socioeconomic background, especially social housing and parental education with school absenteeism and poor academic achievement [ 59 61 ].…”
Section: Discussionmentioning
confidence: 99%
“…We found that younger students, particularly those with poor language skills have difficulty following virtual lessons and would benefit from parental guidance in the absence of a teacher. Unfortunately, non-citizen parents with low educational attainment, like the Rohingya refugees in Malaysia [ 54 , 55 ], may be less able to support children with home education and online learning [ 43 , 56 – 58 ]. Studies elsewhere have linked various dimensions of socioeconomic background, especially social housing and parental education with school absenteeism and poor academic achievement [ 59 61 ].…”
Section: Discussionmentioning
confidence: 99%
“…Intervention content drew upon parenting resources implemented in similar contexts and from preparatory work with refugee communities in Malaysia. Primary resources utilized for session content included, “A toolkit on positive discipline with particular emphasis on South and Central Asia” (Save the Children, 2010), “Bridging refugee youth and children’s services: Raising children in a new country” (U.S. Conference of Catholic Bishops, 2007), and culturally adapted cognitive behavioral therapy (Hinton, Rivera, Hofmann, Barlow, & Otto, 2012; Shaw et al, 2019). Interest in receiving parenting supports originated from participants in a previous mental health‐focused intervention project (Shaw et al, 2019).…”
Section: Methodsmentioning
confidence: 99%
“…Primary resources utilized for session content included, “A toolkit on positive discipline with particular emphasis on South and Central Asia” (Save the Children, 2010), “Bridging refugee youth and children’s services: Raising children in a new country” (U.S. Conference of Catholic Bishops, 2007), and culturally adapted cognitive behavioral therapy (Hinton, Rivera, Hofmann, Barlow, & Otto, 2012; Shaw et al, 2019). Interest in receiving parenting supports originated from participants in a previous mental health‐focused intervention project (Shaw et al, 2019). This parenting intervention further developed through consultation with the research team in Malaysia as well as through focus groups conducted with Rohingya and Afghan communities, where we sought feedback on topics of interest and parenting‐related challenges.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations